(untitled) (Scientific journal of the Fergana State University, 2026)
Abstract This article is dedicated to the historical development of the Turkestan Jadid press in the early 20th century and its impact on society. The Jadid press played a significant role in influencing the modernization of society, particularly in the fields of science, education, culture, and politics. The article analyzes the role of the Jadid press in national awakening, educational reforms, and the struggle against social injustices. It also explores the impact of the Jadid press on the political and social views of its time and its legacy in the present day. This work helps to understand the place of the Jadid press in the historical and cultural heritage of Turkestan and its contribution to the development of society.